Assembly of tetracyclic tetrahydrocarbazoles via a visible-light promoted cascade process. Issue 9 (30th March 2022) - Mei, Haibo; Yu, Yingjie; Wang, Chengting; Liu, Aiyao; Han, Jianlin
Abstract : A photocatalytic cascade reaction of alkene tethered indoles and bromodifluoroacetate esters has been developed, which provides a novel access to tetracyclic tetrahydrocarbazole derivatives. Abstract : We disclose an efficient method for the synthesis of tetracyclic tetrahydrocarbazoles via a visible-light promoted cascade reaction of alkene tethered indoles and bromodifluoroacetate esters. This reaction involves the formation of two C–C bonds and one C–N bond and proceeds via a key reactive tetrahydrocarbazole intermediate and dual cyclization. The reaction features mild conditions, wide substrate scope, and good chemical yields, and provides a new strategy for the synthesis of tetracyclic tetrahydrocarbazole derivatives. The synthetic utility of this reaction was further demonstrated by the large-scale synthesis and reduction of the obtained tetracyclic tetrahydrocarbazole product.